Knowledge Management strategies and processes in Agile Software Develo pment: a systematic literature review - Ouriques, Raquel Andrade Barros; Wnuk, Krzysztof; Gorschek, Tony; Svensson, Richard Berntsson (CoRR, 2018)
Knowledge-intensive companies that adopt Agile Software Development (A SD) relay on efficient implementation of Knowledge Management (KM) str ategies to promotes different Knowledge Processes (KPs) to gain compet itive advantage. This study aims to